Quality of occupational health provision: two rating scales and their determinants - Venables, K; Allender, S (Oxford University Press, 2008)
Background: To develop quality scales for occupational health services (OHSs) and describe and explain variation in quality across the UK university sector. Methods: Analysis of data from a national survey, to which 93 of 117 (79%) UK universities responded, and from the Higher Education Statistics Agency. Two quality scales were generated, one from the 1985 International Labout Organization recommendations on OHSs and one from clinicians' perceptions (good, adequate, poor) about their OHS. The determinants examined were number of university staff, type of OHS (in-house, contracted, none/other), number of full-time equivalent occupational health doctors and nurses and OHS leadership (doctor, nurse, other). Results: There was a wide variation in quality and a correlation (r=0.65) between scales. In-house service, increasing service size and leadership by a doctor or nurse were determinants of higher quality; size of the university was not statistically significant after taking account of these factors. Conclusions: Some university OHSs may not be structured or operated to promote the highest quality of service. Inspection of individual quality scale items may be informative. These scales may be applicable in other employment sectors.